Back Cover: Water Structure Recovery in Chaotropic Anion Recognition: High‐Affinity Binding of Dodecaborate Clusters to γ‐Cyclodextrin (Angew. Chem. Int. Ed. 23/2015). Issue 23 (7th May 2015) - Assaf, Khaleel I.; Ural, Merve S.; Pan, Fangfang; Georgiev, Tony; Simova, Svetlana; Rissanen, Kari; Gabel, Detlef; Nau, Werner M.
Abstract : A supramolecular anchor motif has been found that consists of dodecaborate dianions (B12 X12 2−, X=H, Cl, Br, I) as purely inorganic guests and γ‐cyclodextrin as a macrocyclic host. As shown by K. Rissanen, D. Gabel, W. M. Nau et al. in their Communication onpage 6852 ff., the high micromolar affinity of this hybrid organic–inorganic host–guest complex is traced back to the chaotropic (water structure‐breaking) nature of the globular clusters, their shape complementarity, and their high polarizabilities.